The Implementation of Rock Paper Scissors Game for Teaching Speaking at Indocita Foundation Malang - Annisaus Shofia Bella; Trisnian Ifianti (ANFA MEDIATAMA, 2022)
This study aimed to describe the implementation of rock paper scissorss game in teaching speaking at Indocita Foundation Malang. English is the most prime language in the world. Speaking is the core of language learning also one of the most important skills in English to be developed and enchanced as means of effective communication. The approch used descriptive qualitative method where 35 students of junior high school especially nineth grade at Indocita Foundation Malang participated. The data collection used observation, interview and questionnaire. The result showed that the implementation of rock paper scissors game helped the students to motivate or treat the students to produce the voice immediately. Rock paper scissors game also could motivate the students’ to be brave to speak up in English speaking class. This game in teaching speaking made the students realized that the students might have compete with other members’ group and the students got more effort to be the winner in finishing the game soon. The rock paper scissors took the students attention with the colourful papers in front of them which the students touched while students were speaking up. The problems were faced by the students during the process of implementation of rock paper scissors game in teaching speaking at Indocita Foundation Malang such as 1) cooperation with the member’s of the group 2) lack of vocabularies 3) lack of fluency.